The methyl-CpG-binding protein CIBZ suppresses myogenic differentiation by directly inhibiting myogenin expression - Oikawa, Yu (Nature Publishing Group, 2011)
Postnatal growth and regeneration of skeletal muscle are carried out mainly by satellite cells, which, upon stimulation, begin to express myogenin (Myog), the critical determinant of myogenic differentiation. DNA methylation status has been associated with the expression of Myog, but the causative mechanism remains almost unknown. Here, we report that the level of CIBZ, a methyl-CpG-binding protein, decreases upon myogenic differentiation of satellite-derived C2C12 cells, and during skeletal muscle regeneration in mice. We present data showing that the loss of CIBZ promotes myogenic differentiation, whereas exogenous expression of CIBZ impairs it, in cultured cells. CIBZ binds to a Myog promoter-proximal region and inhibits Myog transcription in a methylation-dependent manner. These data suggest that the suppression of myogenic differentiation by CIBZ is dependent, at least in part, on the regulation of Myog. Our data show that the methylation status of this proximal Myog promoter inversely correlates with Myog transcription in cells and tissues, and during postnatal growth of skeletal muscle. Notably, induction of Myog transcription by CIBZ suppression is independent of the demethylation of CpG sites in the Myog promoter. These observations provide the first reported molecular mechanism illustrating how Myog transcription is coordinately regulated by a methyl-CpG-binding protein and the methylation status of the proximal Myog promoter.